2016
DOI: 10.4103/1357-6283.188764
|View full text |Cite
|
Sign up to set email alerts
|

Which peer teaching methods do medical students prefer?

Abstract: Most respondents in this study did not report a preference for small-versus large-group settings when taught by peers. More Year 3 respondents were likely to prefer small-group peer teaching as opposed to Year 4 respondents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Educators should consider optimal class size when designing CPAL teaching. Inexperienced clinical students may be better suited to smaller CPAL groups …”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Educators should consider optimal class size when designing CPAL teaching. Inexperienced clinical students may be better suited to smaller CPAL groups …”
mentioning
confidence: 74%
“…Based on my discussion with students during clinical attachments, students vary in their preference for CPAL teaching depending on their clinical experience . Educators should consider optimal class size when designing CPAL teaching.…”
mentioning
confidence: 99%
“…Previous studies suggested that the effect of peer teaching is questionable and one reason being the accuracy of peer assessment and feedback [45]. Although small classes are generally preferred in peer teaching [46], the type should be carefully selected. Listening to presentation is perceived as a boring, one-way activity while observing and commenting on treatment skills/ideas gives students opportunities to interact and transact between people and environment.…”
Section: Resultsmentioning
confidence: 99%
“…On a similar note, the findings of a study done with an intention to identify the preference of medical students for peer teaching, 62.5% of the third professional year students opted for small group teaching. 10 The current study was first of its kind as it involved the employment of five different readily available learning media to promote collaboration among team members and also to ensure an in-depth understanding of the topic. A total of 34 students, including 21 girls and 13 boys actively participated in the session to represent subtopics allocated to their groups.…”
Section: Discussionmentioning
confidence: 99%